Continuity management in teachers network. - Tan, Ching Ching. (2008)
This study examines knowledge inheritance in an organization. Using data from Teachers Network, staff population was found to fall under four distinct phases along the knowledge learning curve, characterized by different types of operational knowledge. In totality, for vertical knowledge transfer to take place one must consider the staff’s service length, competencies and also the complementary facilitating media.